Assessing bnAb potency in the context of HIV-1 envelope conformational plasticity. - Caio Foulkes; Nikolas Friedrich; Branislav Ivan; Emanuel Stiegeler; Carsten Magnus; Daniel Schmidt; Umut Karakus; Jacqueline Weber; Huldrych F Günthard; Chloé Pasin; Peter Rusert; Alexandra Trkola (PLoS Pathogens)
For use in prevention and treatment, HIV-1 broadly neutralizing antibodies (bnAbs) have to overcome Env conformational heterogeneity of viral quasispecies and neutralize with constant high potency. Comparative analysis of neutralization data from the CATNAP database revealed a nuanced relationship between bnAb activity and Env conformational flexibility, with substantial epitope-specific variation of bnAb potency ranging from increased to decreased activity against open, neutralization-sensitive Env. To systematically investigate the impact of variability in Env conformation on bnAb potency we screened 126 JR-CSF point mutants for generalized neutralization sensitivity to weakly neutralizing antibodies (weak-nAbs) depending on trimer opening and plasma from people with chronic HIV-1 infection. 23 mutations resulted in a highly neutralization sensitive phenotype, which was associated with de-stabilization of the closed, prefusion conformation. Including 19 of these mutants into a Sensitivity Env mutant panel (SENSE-19), we classified bnAbs according to potency variations in response to trimer opening. To verify that these sensitivity patterns are independent of the in vitro assay system, replication-competent SENSE-19 mutant viruses were tested on primary CD4 T cells. While loss of potency on SENSE-19 was registered for bnAbs from several classes recognizing quaternary epitopes on pre-triggered Env, structural destabilization benefitted MPER bnAbs and other inhibitors known to have post-CD4 attachment neutralization activity. Importantly, for a subset of CD4bs bnAbs, and the interface bnAb PGT151, particularly low potency variation was noted, suggesting that Env conformational tolerance can be achieved but is not the rule. In summary, SENSE-19 screens revealed distinct tolerance levels to Env conformational intermediates between bnAbs that provide mechanistic insights in their function and broaden current neutralization breadth assessments.